2021
DOI: 10.1371/journal.pone.0248431
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in PAR1 KO mice: Decreased brain plasmin and thrombin activity along with decreased infarct volume

Abstract: Background Ischemic stroke is a common and debilitating disease with limited treatment options. Protease activated receptor 1 (PAR1) is a fundamental cell signaling mediator in the central nervous system (CNS). It can be activated by many proteases including thrombin and plasmin, with various down-stream effects, following brain ischemia. Methods A permanent middle cerebral artery occlusion (PMCAo) model was used in PAR1 KO and WT C57BL/6J male mice. Mice were evaluated for neurological deficits (neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…After model establishment, the mice were placed in a cage alone to observe their overall state and behavior. The neurological score [ 43 ] was calculated as follows: 0 points, normal behavior; 1 point, cannot fully extend the right front legs; 2 points, turning around in a circle; 3 points, falling onto the right side; 4 points, cannot move on own and loss of consciousness; 5 points, death.…”
Section: Methodsmentioning
confidence: 99%
“…After model establishment, the mice were placed in a cage alone to observe their overall state and behavior. The neurological score [ 43 ] was calculated as follows: 0 points, normal behavior; 1 point, cannot fully extend the right front legs; 2 points, turning around in a circle; 3 points, falling onto the right side; 4 points, cannot move on own and loss of consciousness; 5 points, death.…”
Section: Methodsmentioning
confidence: 99%
“…CD88, the C5a anaphylatoxin receptor, is expressed locally on presynaptic terminals of mossy fibers in the CA3 region of the adult rat hippocampus, possibly highlighting a role in synaptic plasticity [ 101 ]. PAR1 KO mice after occlusion of the middle cerebral artery display lower thrombin and plasmin activity, along with smaller infarcts [ 102 ]. Likewise, complement factors increase after ischemic strokes such as C1q and C3.…”
Section: The Complement and Coagulation Systems In Pathophysiologymentioning
confidence: 99%
“…Our previous studies demonstrated that the binding of PAR to HK‐1 results in glycolytic and bioenergetics defects in neural cells exposed to the DNA alkylating agent, N‐methyl‐N′‐nitro‐N′‐nitrosoguanidine (MNNG) 9 . PARP‐1 over‐activation plays a significant role in stroke‐induced neural death as PARP‐1 knockout (KO) mice or pharmacological inhibitors of PARPs are significantly protective in brain ischemia models 11–14 . Additionally, PARG KO mice have larger infarct lesions after middle cerebral artery occlusion, indicating that PAR likely plays a substantial role in the stroke pathophysiology 2,15 .…”
Section: Introductionmentioning
confidence: 99%